EMOTIONAL EATING AND ITS ASSOCIATION WITH DEPRESSION IN WOMEN: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Depression is a leading mental health disorder affecting over 280 million people globally, with women disproportionately affected. Emotional eating, defined as eating in response to emotions rather than hunger, is often more prevalent among women and may be associated with depression and emotion regulation difficulties. Method: This cross-sectional study was done among 60 women aged 18–45 years diagnosed with depression as per ICD-11 criteria at Rama Medical College, Kanpur. Sociodemographic data, Beck Depression Inventory (BDI) scores, Difficulties in Emotion Regulation Scale (DERS), and Salzburg Emotional Eating Scale (SEES) scores were collected. Result: Most participants were aged 26–45 years (73.4%), married (70.0%), and homemakers (63.3%). Mean age was 31.6 ± 7.8 years and illness duration 10.3 ± 5.1 months. Emotional eating in response to negative emotions showed a significant positive correlation with depression severity (r = 0.52, p = 0.004). Participants with severe depression had the highest SEES-negative scores (4.4 ± 0.6) compared to moderate (3.7 ± 0.8) and mild (3.1 ± 0.7) (p < 0.001). DERS scores were also significantly correlated with SEES scores. Conclusion: Emotional eating, particularly in response to negative emotions, increases with the severity of depression and is significantly associated with emotion dysregulation in women.